NAZOLAKRİMAL DRENAJ SİSTEM TIKANIKLIKLARINDA ANTEGRAD TEKNİK İLE BALON KATETER DİLATASYON TEDAVİSİ - BAŞAR, Emel; AKOVA, Nilüfer; MİRZATAŞ, Çolpan (Cerrahpaşa Medical Journal, 2014)
Background.- The purpose of this study is to evaluate the our short-term experience with the antegrade balloon catheter dilation (BCD) to treat nasolacrimal drainage system (NLDS) obstruction in adult patients. Design.- Antegrade BCD was performed for only one side of ten patients under topical anesthesia. Obstruction of NLDS, was diagnosed by Jones I and II tests and it was graded subjectively according to Munk.s criteria The site of obstruction was demonstrated by digital substraction macrodacryocystography (DSM). Lacricath balloon catheter set was used for the procedure. Results.- Initial tecnichal and clinical success was satisfactory for 9 cases. Only in one case with common canaliculus total occlusion, the lesion could not have been crossed with the catheter. In a follow up period of 3 months, clinical success was achieved for 7 partial and 2 total obstruction cases. No serious complication was seen during the procedure. Conclusion.- We don.t know yet for the long-term recurrence rates but the short-term effectiveness of BCD with antegrade technique under topical anesthesia is satisfactory for the treatment of epiphora as an office procedure.